Broaden The Authority of The Corruption Criminal Act Courts in Order to Eradicate Corruption, Colusion and Nepotism - Sultan Fauzan Hanif (Universitas Negeri Semarang, 2022)
Seriousness in eradicating KKN as a whole and not only focusing on eradicating corruption alone is in line with the regulations regarding collusion and nepotism in the Law on the Implementation of Clean and KKN-free Government. In the legislation, collusion and nepotism are formulated as criminal acts whose perpetrators are threatened with criminal sanctions. This means that collusion and nepotism are actions that are prohibited by the law. Indonesia has a Special Court to hear corruption cases, but these courts do not have the authority to try criminal acts of collusion and nepotism. The formulation of the problem raised in this paper is 1) What is the urgency of determining the court that is authorized to adjudicate criminal acts of collusion and nepotism? 2) What is the legal policy that should be related to the authority to adjudicate criminal acts of collusion and nepotism? The research method used `is normative legal research. The results of the study indicate that although juridically, the crime of collusion and nepotism should be tried in the general court, in this case the district court, in practice, the crime of nepotism has been tried and decided at the Corruption Court at the Class IA Bengkulu District Court in Decision Number 61/Pid. Sus-TPK/2016/PN.Bg. Therefore, it is necessary to clarify what court is authorized to adjudicate criminal acts of collusion and nepotism. The legal policy that related to the authority to adjudicate criminal acts of collusion and nepotism should be to expand as a step to strengthen the comprehensive eradication of KKN, if these steps are not taken, it is important to revoke the provisions for criminal acts of collusion and nepotism contained in the Law on the Implementation of Clean and KKN-free Government to ensure legal certainty .